Multimolecular signaling complexes enable Syk-mediated signaling of CD36 internalization (2013)
ABSTRACT: CD36 is a versatile receptor known to play a central role in the development of atherosclerosis, the pathogenesis of malaria, and the removal of apoptotic cells. Remarkably, the short cytosolically exposed regions of CD36 lack identifiable motifs, which has hampered elucidation of its mode of signaling. Using a combination of phosphoprotein isolation, mass spectrometry, superresolution imaging, and gene silencing, we have determined that the receptor induces ligand internalization through a heteromeric complex consisting of CD36, β1 and/or β2 integrins, and the tetraspanins CD9 and/or CD81. This receptor complex serves to link CD36 to the adaptor FcRγ, which bears an immunoreceptor tyrosine activation motif. By coupling to FcRγ, CD36 is able to engage Src-family kinases and Syk, which in turn drives the internalization of CD36 and its bound ligands.